2014
DOI: 10.1016/j.fsigen.2013.08.014
|View full text |Cite
|
Sign up to set email alerts
|

“Would you accept having your DNA profile inserted in the National Forensic DNA database? Why?” Results of a questionnaire applied in Portugal

Abstract: The creation and expansion of forensic DNA databases might involve potential threats to the protection of a range of human rights. At the same time, such databases have social benefits. Based on data collected through an online questionnaire applied to 628 individuals in Portugal, this paper aims to analyze the citizens' willingness to donate voluntarily a sample for profiling and inclusion in the National Forensic DNA Database and the views underpinning such a decision. Nearly one-quarter of the respondents w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 23 publications
1
57
0
Order By: Relevance
“…While, the education level among participants showed a statistical significant difference in knowledge between undergraduates and postgraduates. However, in a study conducted in Portugal to determine the knowledge and attitude regarding forensic DNA databases, when 70% of participants were female there was a direct negative correlation between education level and their willingness to participate in DNA database [7].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…While, the education level among participants showed a statistical significant difference in knowledge between undergraduates and postgraduates. However, in a study conducted in Portugal to determine the knowledge and attitude regarding forensic DNA databases, when 70% of participants were female there was a direct negative correlation between education level and their willingness to participate in DNA database [7].…”
Section: Discussionmentioning
confidence: 97%
“…The questionnaires were distributed using quota sampling by research team to the corresponding study group. Based on prior research studies, the expected positive attitude toward national forensic database participation is 46.5% [7]. All statistical analysis was conducted by SPSS 16.0.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Along the same lines, in a simulation study, it was found that threequarters of Portuguese respondents agreed to voluntarily donate a sample for profiling and inclusion in the National Forensic DNA Database. Concerns about the risks of consenting to the donation of a sample for genetic profiling and inclusion in the National Forensic DNA Database are mostly related to lack of control and insufficient or unclear regulations concerning the safeguarding of individuals' data and the supervision of access to and use of genetic data [32,33]. Similarly, a high acceptance rate was also found in a Swiss sample, showing that forensic use of DNA profiling is considered highly trustworthy [34].…”
Section: Introductionmentioning
confidence: 99%